Blah, Blah, Blah: what to do when words don't work - Roam, Dan (London, 2012)
"Ever been to so many meetings that you couldn't get your work done? Ever fallen asleep during a bullet-point presentation? Ever watched the news and ended up knowing less? Welcome to the land of Blah, Blah, Blah, in which talk and words prevent us from thinking. As powerful as words are, we fool ourselves when we think our words alone can detect, describe and defuse the multifaceted problems of today. This book offers a way out of Blah, Blah, Blah. It s called Vivid Thinking , which combines our verbal and visual minds so that we can think and learn more quickly, teach and inspire our colleagues, and enjoy and share ideas in a new and more effective way. Through Vivid Thinking, we can make the most complicated subjects suddenly crystal clear something which is proving increasingly valuable in this complex world of ours."